Degradation of hydrogen sulfide by immobilized Thiobacillus thioparus in continuous biotrickling reactor fed with synthetic gas mixture. (November 2015) - Tóth, G.; Nemestóthy, N.; Bélafi-Bakó, K.; Vozik, D.; Bakonyi, P.
Abstract: In this work, a sulfur-oxidizing bacteria, Thiobacillus thioparus (immobilized on Mavicell B support) was employed to develop a microaerobic, biotrickling filter reactor for the efficient elimination of H2 S from synthetic (bio)gas. To test the capability of this particular strain in oxygen-limited atmosphere, fixed bed reactor was operated under 0.25–5 vol.% O2 concentrations and its H2 S decomposing ability was statistically evaluated. It was found that the system achieved 100% H2 S elimination efficiency when at least 2.5 vol.% oxygen was provided. Further decrease of O2 levels to 0.25–1 vol.% cut the reliability and caused the loss of H2 S biodegradation performance. The results of this study contributed to understand the behavior of T. thioparus under microaerobic conditions and thus may help to design efficient gas purification processes for biogas technology. Highlights: Immobilized Thiobacillus thioparus was applied for H2 S elimination. The applicability of continuous biotrickling reactor was demonstrated. Bioreactor performance under microaerobic conditions was assessed.